Protective effects of lavender oil on sepsis-induced acute lung injury via regulation of the NF-κB pathway - Qian Xie; Yi Wang; Guo-Liang Zou (Taylor & Francis Group, 2022)
Context Lavender oil (Lav) from Lavandula angustifolia L. (Lamiacease) exhibits antioxidative and anti-inflammatory properties against various diseases.Objective The study explores the effect of Lav pre-treatment on sepsis-induced acute lung injury (ALI).Materials and methods Sprague-Dawley rats were assigned into Sham, caecal ligation and puncture (CLP), CLP + Lav (200, 400, and 800 mg/kg) groups. Lav was administered by gavage, once a day, for 7 days. Histological analysis was performed using haematoxylin and eosin staining. Cytokine and nitrite levels were detected by enzyme-linked immunosorbent assay kits and Griess reagent. Gene and protein expression were tested by quantitative real-time polymerase chain reaction and western blot.Results The levels of tumour necrosis factor-α (BALF: 64%, serum: 59%), interleukin (IL)-1β (BALF: 63%, serum: 66%) and IL-6 (BALF: 54%, serum: 59%), and nitrite (40%) and inducible nitric oxide synthase (51%), and the level of myeloperoxidase (66%) and malondialdehyde (59%), and cleaved-caspase 3 (84%) and Bax expression (74%) induced by CLP were decreased when given Lav. Additionally, the level of superoxide dismutase (211%) and glutathione (139%), and the expression of Bcl-2 (980%) induced by CLP were increased when given Lav. The increased p-nuclear factor (NF)-κB/NF-κB (72%) and p-inhibitor of κBα (IκBα)/IκBα (77%) induced by CLP could be reversed by Lav.Discussion and conclusions Lav pre-treatment might protect rats from sepsis-induced ALI via deactivation of the NF-κB pathway. Our research demonstrated the regulatory mechanisms of Lav in sepsis-induced ALI and can provide a theoretical basis for the use of Lav in the treatment of sepsis-induced ALI.